Malignant peripheral nerve sheath tumor in the maxilla. Clinical сase - V. V. Baryshev; F. Е. Sevryukov; V. V. Polkin; Е. А. Khanenya; Т. А. Аgababyan; М. Yu. Fomin; N. К. Silantieva; N. Yu. Dvinskikh; E. D. Akki; V. А. Pankratov; К. V. Baryshev (Опухоли головы и шеи, 2019)
A clinical case of the malignant peripheral nerve sheath tumor is presented. It is a rare tumor in the head and neck area. The tumor arises from Schwann cells, its malignant potential is unclear. This low-growing tumor is presenting as a solitary nodule. To make a precise diagnosis immunohistochemistry assay is used. Surgical approach provides good long-term outcome.